Damage Tolerance and Fail Safety of Welded Aircraft Wing Panels - Zhang, Xiang; Li, Yazhi (AIAA, 2005)
An investigation is presented on fatigue crack growth behavior and fail safety of integral stringer panels typified by welded aircraft fabrications. The stringer panel is made of aluminum alloy 2024-T351 and fabricated by the variable-polarity plasma-arc welding process. The sample simulates a part of the lower-wing skin structures. Based on the linear elastic fracture mechanics, numerical simulations are performed for two configurations, two-stringer and nine-stringer panels, and three damage scenarios, in which welding-induced longitudinal residual stresses are taken into account. A typical load spectrum for large transport aircraft is employed for the analysis. For the two-stringer panel life predictions have a reasonably good correlation with the test results. Based on this validation, large-scale nine-stringer panels with three manufacture options, that is, riveted, integrally machined, and welded integral, are simulated for a skin crack under a broken central stringer propagating to two-bay length. Useful comparisons are made among the three variants. Finally, remedies to improve damage tolerance and fail safety of integral stringer panels are explored. The incorporation of crack retarder straps bonded to the inner surface of an integral panel has greatly improved the fail safety behavior of the component with dramatically increased crack growth live.